Affordance in Socio-Material Networks: A Mixed Method Study of Researchers' Groups and Analog-Digital Objects - Belli, Simone (Frontiers in Psychology, 2021)
In this paper, we argue that we can understand better the relationship between social interaction and materiality by linking qualitative analysis of analog and digital practices, adopting the Basov’s model of socio-material networks. Our research questions turn about the interrogation of how social links distress the usage of analog and digital objects by researchers. We consider scientific networks with the relationship between researchers and their tools as a three-level social material network. It sheds light on how different types of researchers situation their engagement with analog and digital materiality over time and its affordance and emotions. This study contributes to the understanding of researchers’ practices that involve of new and old techniques and specific and not-specific tools.